Imperial gamble : Putin, Ukraine, and the new cold war - Kalb, Marvin L. (Brookings Institution Press, 2015)
Marvin Kalb, a former journalist and Harvard professor, traces how the Crimea of Catherine the Great became a global tinder box. The world was stunned when Vladimir Putin invaded and seized Crimea in March 2014. In the weeks that followed, pro-Russian rebels staged uprisings in southeastern Ukraine. The United States and its Western allies immediately imposed strict sanctions on Russia and whenever possible tried to isolate it diplomatically. This sharp deterioration in East-West relations has raised basic questions about Putin's provocative policies and the future of Russia and Ukraine.